A comparative study of the disinfection efficacy of H2O2/ferrate and UV/H2O2/ferrate processes on inactivation of Bacillus subtilis spores by response surface methodology for modeling and optimization. (June 2018) - Matin, Atiyeh Rajabi; Yousefzadeh, Samira; Ahmadi, Ehsan; Mahvi, Amirhossein; Alimohammadi, Mahmood; Aslani, Hassan; Nabizadeh, Ramin
Abstract: Although chlorination can inactivate most of the microorganisms in water but protozoan parasites like C. parvum oocysts and Giardia cysts can resist against it. Therefore, many researches have been conducted to find a novel method for water disinfection. Present study evaluated the synergistic effect of H2O2 and ferrate followed by UV radiation to inactivate Bacillus subtilis spores as surrogate microorganisms. Response surface methodology(RSM) was employed for the optimization for UV/H2O2/ferrate and H2O2/ferrate processes. By using central composite design(CCD), the effect of three main parameters including time, hydrogen peroxide, and ferrate concentrations was examined on process performance. The results showed that the combination of UV, H2O2 and ferrate was the most effective disinfection process in compare with when H2O2 and ferrate were used. This study indicated that by UV/H2O2/ferrate, about 5.2 log reductions of B. subtilis spores was inactivated at 9299 mg/l of H2O2 and 0.4 mg/l of ferrate concentrations after 57 min of contact time which was the optimum condition, but H2O2/ferrate can inactivate B. subtilis spores about 4.7 logs compare to the other process. Therefore, the results of this research demonstrated that UV/H2O2 /ferrate process is a promising process for spore inactivation and water disinfection. Highlights: For Bacillus Subtilis spore inactivation UV/H2 O2 /ferrate process was more effective than H2 O2 /ferrate process. Synergistic effect of UV/H2 O2 /ferrate resulted in 5.15 log inactivation of Bacillus Subtilis spore. Contact time and H2 O2 concentration were found as the most important independent variables. Insignificant difference between R 2 and R 2 adj (>0.2) indicates that the experimental data are close to regression model.